1997
DOI: 10.1038/ng1297-498
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of human telomerase with the template RNA component hTR and the catalytic protein subunit hTRT

Abstract: The maintenance of chromosome termini, or telomeres, requires the action of the enzyme telomerase, as conventional DNA polymerases cannot fully replicate the ends of linear molecules. Telomerase is expressed and telomere length is maintained in human germ cells and the great majority of primary human tumours. However, telomerase is not detectable in most normal somatic cells; this corresponds to the gradual telomere loss observed with each cell division. It has been proposed that telomere erosion eventually si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
646
0
5

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 858 publications
(669 citation statements)
references
References 30 publications
18
646
0
5
Order By: Relevance
“…Previously, we had shown that in the pre-immortal HA1 clone, telomere length declines with cell division and telomerase remains inactive until the cells reach proliferative crisis, while in immortal HA1 cells telomere length stabilizes and telomerase is activated (Counter et al, 1992;Avilion et al, 1996). Recently, we also found that up-regulation of the mRNA encoding the catalytic subunit of human telomerase, hTERT (Meyerson et al, 1997;Weinrich et al, 1997;Nakamura and Cech, 1998), coincides with the emergence of immortal HA1 cells (Meyerson et al, 1997).…”
Section: Resultsmentioning
confidence: 93%
“…Previously, we had shown that in the pre-immortal HA1 clone, telomere length declines with cell division and telomerase remains inactive until the cells reach proliferative crisis, while in immortal HA1 cells telomere length stabilizes and telomerase is activated (Counter et al, 1992;Avilion et al, 1996). Recently, we also found that up-regulation of the mRNA encoding the catalytic subunit of human telomerase, hTERT (Meyerson et al, 1997;Weinrich et al, 1997;Nakamura and Cech, 1998), coincides with the emergence of immortal HA1 cells (Meyerson et al, 1997).…”
Section: Resultsmentioning
confidence: 93%
“…37,38 Although hTR and hTERT are essential for telomerase activity, the expression of hTERT is closely associated with telomerase activity. 39,40 Therefore, to inhibit telomerase activity significantly, the hTERT may be more attractive as a target than the hTR. More recently, it has been demonstrated that the complete inhibition of telomerase using a dominant-negative mutant of hTERT resulted in reduction in telomere length and apoptotic death of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…To test directly whether the assembled mTERT cDNA encoded catalytic activity, in vitro telomerase reconstitution assays were performed according to Weinrich et al (1997). mTERT was expressed alone or in combination with hTR and telomerase activity was measured by a modi®ed version of the TRAP assay ; for a positive control, parallel assays were performed with hTERT and hTR.…”
Section: Reconstitution Of Telomerase Activity With Mtert Protein Andmentioning
confidence: 99%